The Impact of Destructive Fishing on the Development of Marine Tourism in Indonesia: A Case Study of Kapoposang Island, Pangkajene and Islands Regency, South Sulawesi Province, Indonesia - Andi Ajeng Lara Zary; Agussalim Burhanuddin; Seniwati Seniwati (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
As an archipelago, Indonesia has a vast ocean and is rich in biodiversity. With a vast ocean, Indonesia has considerable marine ecotourism potential. However, the problem that needs to be solved is destructive fishing in Indonesian waters. Destructive fishing can damage the marine ecosystem and reduce the number of marine life that characterizes Indonesian waters. Kapoposang Island is one of Indonesia's areas with great marine ecotourism potential. However, on Kapoposang Island, there are cases of destructive fishing which are feared to hurt the development of marine ecotourism. Besides that, community participation is needed so that an increase can follow the growth of marine ecotourism on Kapoposang Island in the standard of living of the local community, one of which is the economy. This study examined the relationship between destructive fishing and tourism development on Kapoposang Island. The research was conducted using a qualitative approach to analyze the impact of destructive fishing on the development of marine ecotourism on Kapoposang Island, Pangkajene Islands Regency, South Sulawesi. Researchers used data sources in the form of interviews and literature studies.